APLICATION OF PROBLEM SOLVING LEARNING TO IMPROVE STUDENT LEARNING ACTIVITIES ON MATERIALS USING EQUIPMENT AND EQUIPMENT IN THE WORKSHOP IN THE TENTH GRADE OF TKR SMK NEGERI 1 PALANGKA RAYA 2016/2017 - Nyoman Dwi Lipe (Jurusan Pendidikan Teknologi Dan Kejuruan, 2018)
This study aims to find out how far the improvement level of student learning outcomes after conducting the problem solving model in the tenth grade of TKR SMK Negeri 1 Palangka Raya on academic year 2016/2017. Th e population for this study was students of tenth grade of TKR SMK Negeri 1 Palangka Raya involving 46 students. Data collection has performed using a test model namely post-test and an observation sheet which is consisting of student activity sheets and student response questionnaires sheet. The data was then collected and analyzed using the post-test average. Based on the result of post-test data analysis of mean value 77,31, and all students exceeded the specified passing grade criteria from the results of this study. It can be concluded that student learning outcomes can be well-performed if using problem solving.